Letter - Bedford Labour Party Industrial Committee, 5 May 1926 (page 1) (Bedford)
1926-05-05 "Letter - Bedford Labour Party Industrial Committee, 5 May 1926 (page 1)" [g0266001.jpg], 5 May 1926 Local Organisation